ANALISIS ADOPSI INOVASI PENYULUHAN PERTANIAN DI KABUPATEN ACEH UTARA DALAM MENDUKUNG KEDAULATAN PANGAN - Zuriani, Zuriani; Martina, Martina (Jurnal AGRISEP, 2016)
This research was conducted in North Aceh Sub District, Syamtalira Bayu with a sample of 60 farmers. The purpose of this study was to determine and to analyze the influence of innovation characteristics, characteristics of farmers, and media delivery to the process of innovation adoption of agricultural extension in North Aceh District. The data used is the cross section taken in June 2016 by the planting season beginning in 2016. The research method used is quantitative method by using non-linear regression model. Analysis showed that the adoption of innovation, in this case the pattern Legowo row planting paddy rice by farmers in the district Syamtalira Bayu simultaneously influenced by the complexity, education, and number of outlets. The complexity and number of variables have significantly influence the election cropping paddy rice at the sites.